Sex and race differences in J-Tend, J-Tpeak, and Tpeak-Tend intervals - Hnatkova, Katerina; Toman, Ondřej; Šišáková, Martina; Smetana, Peter; Huster, Katharina M; Barthel, Petra; Novotný, Tomáš; Schmidt, Georg; Malik, Marek (Scientific reports, 2019)
To facilitate the precision of clinical electrocardiographic studies of J-to-Tpeak (JTp) and Tpeak-to-Tend (Tpe) intervals, the study investigated their differences between healthy females and males, and between subjects of African and Caucasian origin. In 523 healthy subjects (254 females; 236 subjects of African origin), repeated Holter recordings were used to measure QT, JT, JTp, and Tpe intervals preceded by both stable and variable heart rates. Subject-specific curvilinear regression models were used to obtain individual QTc, JTc, JTpc and Tpec intervals. Rate hysteresis, i.e., the speed with which the intervals adapted after heart rate changes, was also investigated. In all sex-race groups, Tpe intervals were not systematically heart rate dependent. Similar to QTc intervals, women had JTc, and JTpc intervals longer than males (difference 20-30 ms, p < 0.001). However, women had Tpec intervals (and rate uncorrected Tpe intervals) shorter by approximately 10 ms compared to males (p < 0.001). Subjects of African origin had significantly shorter QTc intervals than Caucasians (p < 0.001). Gradually diminishing race-difference was found for JTc, JTpc and Tpec intervals. JTc and JTpc were moderately increasing with age but Tpe/Tpec were not. Rate hysteresis of JTp was approximately 10% longer compared to that of JT (p < 0.001). In future clinical studies, Tpe interval should not be systematically corrected for heart rate and similar to the QT interval, the differences in JT, JTp and Tpe intervals should be corrected for sex. The differences in QT and JT, and JTp intervals should also be corrected for race.
Keywords: srdeční frekvence; Racial Groups; převodní systém srdeční; mužské pohlaví; elektrokardiografie; Electrocardiography; ženské pohlaví; dospělí; Humans; Adult; rasové skupiny; pohlavní dimorfismus; Female; Male; Heart Conduction System; Sex Characteristics; lidé; Heart Rate